PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN, DEBT TO EQUITY RATIO, DAN EARNING PER SHARE TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PERUSAHAAN PUBLIK SUB SEKTOR PLASTIK DAN KEMASAN DI BURSA EFEK INDONESIA PERIODE 2014-2018) - Hanifa Hanifa (Jurnal Ekonomika dan Manajemen, 2020)
The purpose of this research is to find out effects of Firm size, Firm Growth, Debt to Equity Ratio, Earning Per Share toward the Company Value. The samples of this research are plastic and packaging companies listed in Indonesia Stock Exchange period 2014 - 2018. This research applies purposive sampling technique, in which 12 plastic and packaging companies are eligible. Moreover, this research using Statistical Package for the Social Science Programs (SPSS) version 20.0 and Microsoft Excel 2013. The direct and the indirect effects of linear regression coefficient in order to ensure the correlation between the independent variables toward the dependent variables. The outcomes of this research indicates that the Firm size and Earning Per Share variable are having the significant effect toward Company Value, while the Firm Growth and Debt to Equity Ratio do not have the significant effect toward Company Value.